Epicardial catheter ablation for ventricular tachycardia on uninterrupted warfarin: A safe approach for those with a strong indication for peri-procedural anticoagulation?. (1st November 2016) - Sawhney, V.; Breitenstein, A.; Ullah, W.; Finlay, M.; Sporton, S.; Earley, M.J.; Chow, A.W.; Dhinoja, M.; Lambiase, P.; Schilling, R.J.; Hunter, R.J.
Abstract: Background: Current guidelines for epicardial catheter ablation for ventricular tachycardia (VT) advocate that epicardial access is avoided in anticoagulated patients and should be performed prior to heparinisation. Recent studies have shown that epicardial access may be safe in heparinised patients. However, no data exist for patients on oral anticoagulants. We investigated the safety of obtaining epicardial access on uninterrupted warfarin. Methods: A prospective registry of patients undergoing epicardial VT ablation over two years was analysed. Consecutive patients in whom epicardial access was attempted were included. All patients were heparinised prior to epicardial access with a target activated clotting time (ACT) of 300–350 s. Patients who had procedures performed on uninterrupted warfarin (in addition to heparin) were compared to those not taking an oral anticoagulant. Results: 46 patients were included of which 13 were taking warfarin. There was no significant difference in clinical and procedural characteristics (except INR and AF) between the two groups. Epicardial access was achieved in all patients. There were no deaths and no patients required surgery. A higher proportion of patients in the warfarin group had a drop in haemoglobin of > 2 g/dL compared to the no-warfarin group (38.5% versus 27.3%, p = 0.74) and delayed pericardial drain removal (7.8% versus 3.03%, p = 0.47). There was no difference in overall procedural complication rate. No patients required warfarin reversal or blood transfusion. Conclusion: Epicardial access can be achieved safely and effectively in patients' anticoagulated with warfarin and heparinised with therapeutic ACT. This may be an attractive option for patients with a high stroke risk.